STUDY OF THE POTENTIAL ANALGESIC PROPERTIES OF CARBON DIOXIDE FOR THE TREATMENT OF PAIN SYNDROME IN CASE OF OSTEOARTHRITIS - Shtroblia, Viktor; Lutsenko, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Pain syndrome is a serious global problem that causes and complicates a number of diseases, the main symptom of which is joint pain. One of them is osteoarthritis (OA). Traditional methods of treating OA often have limited efficacy and can cause side effects, so it is important to study new approaches, such as carboxytherapy (use of carbon dioxide). Objective. To investigate the analgesic effect of carbon dioxide (CO2) and its combined use with other agents. Methods. The efficacy of carbon dioxide injections used alone and in combination with other drugs was studied in a formalin model of inflammation in rats. Results. The latent periods of phases I and II increased significantly in the experimental groups, especially in groups V, VI and VII (p < 0.001), indicating a delay in pain reactions. The duration of pain phase I was significantly shorter in the groups receiving CO2 compared to the control group (p < 0.001). The shortest duration was observed in group V, where it decreased by 1.77 minutes. The duration of pain phase II was also significantly shorter in groups V, VI, and VII treated with CO2 compared to group II (p < 0.001). The difference ranged from 7.49 to 12.54 minutes. The number of pain reactions after phase I decreased by 13.25– 16.1 points in the groups receiving CO2 compared to the control group. The data obtained indicate that CO2 significantly increases the duration of latent periods of pain (by 55–65 %), reduces the duration of its phases (by 40–50 %) and reduces the intensity of pain reactions (by 40–50 %) in rats compared to control pathology. The most pronounced effect was observed with the combined use of CO2 with sodium diclofenac or chondroitin sulfate. Conclusions. The results of the study expand the understanding of the analgesic effect of CO2 on the formalin model of inflammation. The use of CO2 significantly reduced the duration of both phases of the pain reaction and reduced the number of painful manifestations, which confirms the prospects of its use as an additional, and in some cases the main means of reducing pain and inflammation.